Environment discourses for sustainability development in English language coursebooks - Fadhila Yonata; Dwi Rukmini; Suwandi Suwandi; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
Abstract. This article analyzes environmental discourses in English as Foreign Language textbooks used nationwide in senior secondary school education in Indonesia. Published by a recommended private publisher, the textbook serves as the supporting teaching material for a compulsory English subject for senior high school students. We focused our multimodal critical discourse analysis on themes and discursive affordance of the texts and images depicted in the textbooks. Anchoring in the type of environmental discourses proposed by Curdt-Christiansen (2021), this study scrutinized to what extent environment-related texts promote profound environmentalism. The study's conclusion is that the textbook authors consider environmental literacy though still in ‘shallow’ form, and limitedly provide an educational experience that would possibly enhance students’ environmental awareness and, by that means, prepare them to act by sustainability development.